SELECTING ONLINE SHOP RETAILER OF YOUNG CONSUMERS IN MANADO WITH ANALYTIC HIERARCHY PROCESS ANALYSIS - Mirana, Sengkey Michelle; Saerang, David P.E; Tumewu, Ferdinand . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Young people have been the majority shoppers online nowadays and thus this study to determine the most preferable online shop retailer for young consumers and to identify the criteria that influence consumer in selecting online shop retailer in Manado. The number of sample is 30 respondents of young consumers. This research used quantitative method. The method used in this research is Analytic Hierarchy Process (AHP). Analytic Hierarchy Process (AHP) is a method used to process results and paired options between. Decision-making issues with AHP are generally composed into criteria, and alternative options. In this research, AHP is used to compare each online shop retailer which are Lazada, Tokopedia, and Bukalapak. The result shows that Lazada is the most preferred online shop retailer by the young consumers, followed by Tokopedia, and Bukalapak. Further, the criteria with the highest influence on consumers in selecting online shop retailer is website design. Online shop in Manado, particularly in the online retail, could use the result as a guideline to help marketers design campaigns that speak to the fundamental concerns and desires of their targeted consumers such as website design, transaction security, time saving and shopping convenience.Keywords: analytic hierarchy process, consumer preference, online shop retail, website design